Cluster-based synchronization scheme for femtocell network - Hasan, Mohammad Kamrul; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem (2012)
Femtocell technology has drawn considerable attention as a cost-effective mean to improve cellular coverage and capacity. Data loading and offloading to the macro Base Station (mBS) is supported through internet backhaul which exhibits the uniqueness of this technology. Interference is one of the most challenging phenomenon's that arise due to the non-synchronized femtocell. It is known that fBS and macrocells Base Station (mBS) network operates on the same frequency under a licensed spectrum hence; fBS network can interfere with the macrocells network. However, in this paper, cluster-based synchronization scheme has been proposed which functions through clustering, inter-cluster synchronization scheme. The proposed scheme mainly focuses on reducing the clock offset and skew as well as message overhead. Cluster-based synchronization scheme provides high scalability and works in a decentralized manner which can support a large number of fBS networks with a satisfactory performance level in term of synchronization accuracy. In this paper, it has shown that proposed scheme's synchronization accuracy is higher than any of the existing schemes so far.